Dynamics Of Tourism Development And Sustainability Strategies In The Northern Coastal Region Of Aceh - Fadhly, Muhammad; Zahrul Fuady; Atika Aditya (Universitas Trisakti, 2026)
Tourism development in the northern coastal area of Aceh is a strategic effort to boost local economic growth while preserving the environment. This study focused on Gampong Lamreh, located in Mesjid Raya Subdistrict, Aceh Besar District, which offers natural and historical attractions with scenic landscapes, cultural heritage, and a relatively well-preserved environment. A qualitative descriptive method was used, involving field observations, interviews, documentation, and questionnaires.The study found that 96% of the community was aware of Lamreh’s tourism potential, with 78% identifying natural attractions as the main draw. However, community participation in tourism activities remained low, indicating the need to enhance local involvement. Economically, 39% of residents reported increased income from tourism, though the benefits were not evenly distributed. Environmentally, 68% of respondents perceived tourism as having a positive impact, and 79% hoped it would lead to economic growth and infrastructure improvements.Despite its potential, Lamreh faces challenges such as inadequate infrastructure, lack of supporting facilities, and the absence of an integrated destination management system. Using a SWOT analysis, the study recommended a strategy based on the Weakness-Opportunities (W-O) approach, which leverages external opportunities to address internal weaknesses. Key strategies included improving accessibility, developing trekking paths, revitalizing historical sites, securing cliffs, and enhancing institutional support and digital promotion. These efforts aim to transform Gampong Lamreh into a competitive and sustainable coastal tourism destination in Aceh, benefiting both the local community and the environment.